The Influence of Brand Image, Advertising and Shopping on the Financial Performance of Indonesian Retailers - Hendarto, Totok (Revenue Journal: Management and Entrepreneurship, 2024)
The retail industry in Indonesia is currently undergoing significant and competitive growth, leading businesses to explore effective strategies to enhance their financial performance. This study investigates how brand image, advertising and promotion spending, and capital expenditure investments impact the financial performance of retail companies in Indonesia. Drawing on data from 50 prominent retail firms listed on the Indonesia Stock Exchange (IDX) over the period from 2013 to 2023, a survey method combined with quantitative analysis was employed. Data collection utilized purposive sampling, and multiple linear regression analysis was conducted to assess the relationships between independent variables and Return on Assets (ROA) as the dependent variable. Findings reveal that brand image significantly boosts financial performance, with a 15% rise in ROA for every 10-point improvement in the Top Brand Index (TBI) score. Additionally, increased advertising and promotion spending correlates positively, yielding a 10% rise in ROA with a 20% increase in spending. Meanwhile, capital expenditure shows a moderate positive influence, with a 5% increase in ROA for every 30% investment rise. Ultimately, this study underscores the critical roles of brand image and advertising expenditure in shaping effective business strategies for improving financial performance in Indonesia's retail sector, providing valuable insights for managers and stakeholders.